DESAIN DAN PEMBUATAN ALAT MONITORING KERUSAKAN MESIN BERDASARKAN LEVEL GETARAN - Suryadi, Dedi; Pratama, M. Dicky (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
In industry, vibration frequently occurs on rotating machines. In case of vibration level, it can cause damage to machines. Therefore vibration level should be continuously checked by using a predictive maintenance method in order to prevent the severe fault. In this study, a vibration monitoring tool with short message service (SMS) will be manufactured. This tool consists of a vibration sensor, controller, data acquisition, and provides both monitoring and warning systems in a remote area. An accelerometer is used as a vibration sensor placing on a bearing housing. Here, a designed tool is applied to machines with several conditions, namely normal, unbalance, and mechanical looseness. The rotational speed of the motor is varied at 1000 rpm, 1500 rpm, and 2000 rpm. Moreover, the warning system will be active by sending SMS to the operator when the vibration level is higher than one of ISO 2372. Validation is done by comparing the designed tool and standard tool. Finally, the results show that the designed tool can be effectively used for vibration measurement because it has an error of less than 3.5%, and the warning system through SMS is also running well with a delivery time of fewer than 5.5 seconds.